Transforming schools : alternative perspectives on school reform - Mulcahy, D. G. (Contemporary research in education., 2013)
President Obama has on a number of occasions rejected policies that have been tried and do not work. Legislation such as No Child Left Behind and policies such as Race to the Top are neither effective nor based on sound research. Educational policy-making is now, more than ever, the preserve of politicians, advocacy foundations, and lobbyists parading as corporate leaders. Teachers have little voice; their role is merely to be held responsible for policies foisted upon them.In Transforming Schools: Alternative Perspectives on School Reform, our aim is to provide alternative perspectives to the dead-end educational policies by which our governments have become consumed. We turn the spotlight on a select range of topics that have become the focus of concern and we consider the implications for school improvement. These topics include school reform in general, the achievement gap, literacy, standardized assessment, social justice and ecojustice, aesthetic and moral education, and general education.